The Improvement of Students’ Mathematical Communication Ability and Learning Interest on Junior High School through The Application of Reciprocal Teaching - Astuti, Veni Aprilia Dwi; Putra, Harry Dwi; Hendriana, Heris (IKIP Siliwangi, 2024)
This research is an experiment which aims to examine improving the mathematical communication skills and interest in learning of junior high school students in set material by implementing the reciprocal teaching learning model. The problem behind this research is that students' mathematical communication skills and interest in learning in set material are still in the low category, so learning alternatives are needed that can develop students' mathematical communication skills and interest in learning. The research method used is Pre-Experimental with a one group pretest-posttest research design. The population in this study were all class VII students in one of the private junior high schools in Karawang Regency. The sample in this research was 25 students with a purposive sampling technique. The instrument used is a communication skills test and a non-test in the form of a learning interest questionnaire. Based on the analysis of the data obtained, it shows that students' mathematical communication skills after implementing the reciprocal teaching model are better, namely from 8.32 to 75.32 and students' interest in studying set material after using the reciprocal teaching model is 60% in the low interest category and 40% with the high category which was previously 32% in the very low category and 68% in the low interest category. Thus, it can be concluded that the application of the reciprocal teaching model can improve the mathematical communication skills and interest in learning of class VII SMP students in set material, although not optimally.